Determinants of health and arterial hypertension - Ávila, Zulema; García, Karen A. (Revista Gregoriana de Ciencias de la Salud, 2024)
High blood pressure has become a growing public health problem, influenced by a variety of determinants including biological factors such as age, personal and family medical history, and genetic predispositions. However, in the last decade, lifestyle-related determinants have gained prominence, such as obesity, sedentary lifestyle, and alcohol consumption, contributing to a growing and globally less controlled prevalence of hypertension. This literature review aimed to analyze the relationship between these determinants and the incidence of arterial hypertension. Significant scientific evidence was found that directly links the biological determinants, lifestyles, environment and organization of health services with the challenge that high blood pressure represents for public health worldwide.